Эффективность установки турбопривода питательного насоса вместо электропривода на энергоблоках мощностью 200 МВт - Пугачева, Татьяна Николаевна (Донецький національний технічний університет, 2017)
Рассмотрен вопрос преимущества применения турбоприводов питательных насосов на энергоблоках 200 МВт ТЭС. Определены возможные схемы включения турбопривода в тепловую схему энергоблока ТЭС. Приведено сравнение турбопривода с частотным регулированием и гидромуфтой. Дано сравнение экономичности турбопривода, частотного регулятора и гидромуфты. Представлена структура дополнительных потерь при работе различных типов регулируемых приводов. Представлено сравнение показателей работы для различных типов регулируемого привода питательного насоса. Приведены экономические показатели внедрения турбопривода питательного насоса.

There are 43 power generating unit with the capacity of 200 MW operate in Ukraine. Some of them for various reasons work with incomplete load The reasons for this are low fuel quality, technical condition of the boiler unit, participation in the regulating mode of the power system. Currently, for feeding water to the boiler power generating units of 200 MW use electric drive pumps (EDP). When the power generating unit is running in partial load mode, the EDP operates at constant revolutions and a practically constant pressure, and the EDP output is regulated by a boiler capacity regulator (BCR), the pressure difference at which increases. At the same time, the power consumed by the EDP decreases slightly. The mode of the most economical operation of the power generating unit corresponds to the maximum opening of the BCR with a pressure drop on it of not more than 5...10 kg/cm2. This adjustment is possible when the feed pump is worked with a variable speed, and in this situation it is advisable to install the turbo drive of the feed pump instead of the electric drive. The purpose of this article is to analyze the efficiency of installing the turbo drive of the feed pump, to identify the advantages of the turbo drive of the feed pump, to consider the various options for including the turbo drive of the feed pump in the thermal scheme of the power generating unit. The advantages of the turbo drive of the feed pump: - the possibility of changing the output and pressure of the feed pump by regulating the number of its revolutions with a significant reduction in energy consumption; - the operational maneuverability of the unit is ensured when covering a wide range of possible loads; - the possibility of the power unit operating on sliding parameters, which, both with the adjustment of the steam distribution, leads to an increase in the electric power of the main turbine and the profitability of the power unit as a whole. Operation of the unit on sliding parameters with reduced pressure and temperature favorably affects the state of the metal, the service life and reliability of the elements of the boiler and turbine; - the possibility of providing their own needs in a pair of certain parameters with the exhaust steam of the turbo drive. At the same time, no need uneconomical reduction-cooling devices, which resulting in underproduction of electric power. Depending on the parameters of the steam before the turbo drive and behind it, the presence or absence of station consumers of the reduced steam, as well as the operation modes of the main turbine, there are several options for switching the turbo drive of the pump into the thermal scheme of the power generating unit are possible. For example, feeding the turbo drive with fresh steam from the boiler and discharging the exhaust steam into the auxiliary sewer (13 atm), supplying the turbo drive with steam from the 2nd (or 3rd) regenerative intake and discharging the exhaust steam into the flowing part of the low-pressure cylinder of the turbine, steam turbine from the 2nd (or 3rd) regenerative selection and discharge of the exhaust steam into the turbine condenser.
Efficiency of installation of turbo drive of the feed pump instead of electric drive for 200 MW power plants
Keywords: питательный насос; турбопривод; питание турбопривода; частотный регулятор; гидромуфта; экономия топлива; годовая экономия; feed pump; turbo drive; turbo drive power; frequency regulator; hydraulic coupling